An investigation of cerebral oxygen utilization, blood flow and cognition in healthy aging. - Sarah J Catchlove; Helen Macpherson; Matthew E Hughes; Yufen Chen; Todd B Parrish; Andrew Pipingas (PLoS ONE, 2018)
Understanding how vascular and metabolic factors impact on cognitive function is essential to develop efficient therapies to prevent and treat cognitive losses in older age. Cerebral metabolic rate of oxygen (CMRO2), cerebral blood flow (CBF) and venous oxygenation (Yv) comprise key physiologic processes that maintain optimum functioning of neural activity. Changes to these parameters across the lifespan may precede neurodegeneration and contribute to age-related cognitive decline. This study examined differences in blood flow and metabolism between 31 healthy younger (<50 years) and 29 healthy older (>50 years) adults; and investigated whether these parameters contribute to cognitive performance.Participants underwent a cognitive assessment and MRI scan. Grey matter CMRO2 was calculated from measures of CBF (phase contrast MRI), arterial and venous oxygenation (TRUST MRI) to assess group differences in physiological function and the contribution of these parameters to cognition.Performance on memory (p<0.001) and attention tasks (p<0.001) and total CBF were reduced (p<0.05), and Yv trended toward a decrease (p = .06) in the older group, while grey matter CBF and CMRO2 did not differ between the age groups. Attention was negatively associated with CBF when adjusted (p<0.05) in the older adults, but not in the younger group. There was no such relationship with memory. Neither cognitive measure was associated with oxygen metabolism or venous oxygenation in either age group.Findings indicated an age-related imbalance between oxygen delivery, consumption and demand, evidenced by a decreased supply of oxygen with unchanged metabolism resulting in increased oxygen extraction. CBF predicted attention when the age-effect was controlled, suggesting a task- specific CBF- cognition relationship.